PENGARUH PENAMBAHAN SERBUK ONYX TERHADAP TERHADAP POTENSI KEMBANG TANAH LEMPUNG EKSPANSIF - Loca, Rovino Neno; Metosala F.A.S. Meus, Enos; M oliveira Moniz, Marcolina; Tugas Sudjianto, ST.MT, Dr. Agus (Universitas Widyagama Malang, 2014)
Expansive soil has unique characteristics in absorbing and releasing water . When drought comes , almost all terkandungnya water can be released , but the current wet the soil is able to absorb water up to more than 100 % dry weight . Some things really affect the development potential of expansive clays such as: water content , mineral chemistry , density , plasticity index and activity . To get the results of the study used several stages of research methods include: preparation , sampling , testing soil properties , mineral - chemical test , the main test or test and development potential using Jangka Sorong , the composition of a mixture of 5% , 10 % , 15 % , and 20 % . After testing and analysis of data , using graphs it can be concluded that , the greater the value , the smaller the potential mix of flowers that happen . Monmorillonite mineral values ââfor the native land 49.74 % , and for the composition of a mixture of 5% onyx mineral monmorillonite value of 46 296 % , for the composition of a mixture of 10 % mineral onyx monnmorillonite value of 43 893 % , for the composition of a mixture of 15% mineral onyx montmorilonite value of 43 639 % , and for the composition of a mixture of 20% mineral onyx montmorilonite value of 33 943 % . Keywords : landfiil soils, onyx powder, stabilization, shear strength and bearingcapacity